Concepts in Early Reconstruction of the Burned Hand. Issue 3 (March 2020) - Hundeshagen, Gabriel; Warszawski, Jan; Tapking, Christian; Ziegler, Benjamin; Hirche, Christoph; Kneser, Ulrich; Schmidt, Volker J.
Abstract : Background: Early reconstruction of burn sequelae of the hand can be challenging owing to high goals for functional and aesthetic outcome. A variety of reconstructive procedures with ascending levels of complexity exists and warrants careful indication. Methods: In this case series, the main reconstructive techniques for reconstruction of burn defects of the hand are described, illustrated, and discussed: split thickness skin grafting (STSG) with fibrin glue, dermal matrices with STSG, distant random pattern (abdominal bridge) flap, distant pedicled flap (superficial circumflex iliac artery flap), and free microvascular tissue transfer (anterolateral thigh flap). An algorithm for decision making in the reconstructive process is proposed. Results: Split thickness skin grafting provides sufficient coverage for partial thickness defects without exposure of functional structures; fixation with fibrin glue avoids unnecessary stapling. Dermal matrices under STSG provide vascularized granulation tissue on full thickness defects and can be used as salvage procedure on functional structures. Distant random pattern or pedicled flaps provide sufficient coverage of large full thickness defects with exposed functional structures but pose some challenges regarding patient compliance and immobilization. Free tissue transfer allows tailored reconstruction of large full thickness defects with exposed functional structures and can be safely and feasibly performed. Secondary and tertiary procedures are needed with more complex techniques; if applied correctly and consequently, all methods can yield favorable functional and aesthetic outcomes. Conclusions: Reconstruction of the burned hand may require a broad armamentarium of surgical techniques with different levels of complexity, versatility, and applicability. Excellent results can be achieved with the right procedure for the right patient.